2018
DOI: 10.1111/iju.13787
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of carbapenem‐resistant Gram‐negative bacilli: A collaborative study of antibiotic‐resistant bacteria between Indonesia and Japan

Abstract: Objectives To explore the occurrence and characterization of carbapenemase‐producing pathogens among carbapenem‐resistant Gram‐negative bacilli isolated from hospitalized patients with urinary tract infection in Indonesia. Methods This was a study promoted by the Japanese–Indonesian collaborative research program in the Japan Initiative for Global Research Network on Infectious Diseases. Bacterial pathogens were prospectively isolated from urine specimens of hospitalized urinary tract infection patients at Dr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…7 Specimens were determined as positive for ESBL using the double-disk synergy test. [7][8][9] The antimicrobial agents used were AMP, CFZ, CTX, CRO, CAZ, SAM, TZP, IPM, MEM, GEN, AMK, TOB, LVX, CIP, CHL, SXT, TET and FOF. E. coli ATCC 25922 was used for quality control.…”
Section: Bacterial Strains Antimicrobial Susceptibility and Esbl Screening Testsmentioning
confidence: 99%
“…7 Specimens were determined as positive for ESBL using the double-disk synergy test. [7][8][9] The antimicrobial agents used were AMP, CFZ, CTX, CRO, CAZ, SAM, TZP, IPM, MEM, GEN, AMK, TOB, LVX, CIP, CHL, SXT, TET and FOF. E. coli ATCC 25922 was used for quality control.…”
Section: Bacterial Strains Antimicrobial Susceptibility and Esbl Screening Testsmentioning
confidence: 99%
“…Klebsiella pneumoniae is clinically important because it is involved in a variety of healthcare-association infections (HAI) such as in the urinary and respiratory tracts, wounds, endocarditis, and sepsis 1,2,3 . Intestinal colonization is one of the main factors favoring infection by K. pneumoniae, as colonized carriers can serve as important reservoirs for the spread of bacteria in the hospital environment.…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria can be found in various sources, including blood, sputum, urine, and others. The current study in Indonesia found that in 2015-2016, from total of 1082 clinical bacteria in the hospital, 10.7% were carbapenem-resistant (Kuntaman et al 2018). A study in Aceh showed that from 212 methicillin-resistant Staphylococcus haemolyticus, 99.1% of them were resistant to carbapenem (Suhartono et al 2019).…”
Section: Introductionmentioning
confidence: 69%